Analysis of Dysphagia Patterns Using a Modified Barium Swallowing Test Following Treatment of Head and Neck Cancer - Lee, So-Yoon; Kim, Bo Hwan; Park, Young Hak (Yonsei medical journal, 2015)
The purposes of this study were to evaluate specific dysphagia patterns and to identify the factors affecting dysphagia, especially aspiration, following treatment of head and neck cancer. A retrospective analysis of 57 patients was performed. Dysphagia was evaluated using a modified barium swallow (MBS) test. The MBS results were rated on the 8-point penetration-aspiration scale (PAS) and swallowing performance status (SPS) score. Reduced base of the tongue (BOT) retraction (64.9%), reduced laryngeal elevation (57.9%), and cricopharyngeus (CP) dysfunction (47.4%) were found. Reduced BOT retraction was correlated with clinical stage (p=0.011) and treatment modality (p=0.001). Aspiration in 42.1% and penetration in 33.3% of patients were observed. Twenty-four patients had PAS values over 6, implying aspiration. Forty-one patients had a SPS score of more than 3, 25 patients had a score greater than 5, and 13 patients had a SPS score of more than 7. Aspiration was found more often in patients with penetration (p=0.002) and in older patients (p=0.026). In older patients, abnormal swallowing caused aspiration even in those with a SPS score of more than 3, irrespective of stage or treatment, contrary to younger patients. Tube feeders (n=20) exhibited older age (65.0%), dysphagia/aspiration related structures (DARS) primaries (75.0%), higher stage disease (66.7%), and a history of radiotherapy (68.8%). Reduced BOT retraction was the most common dysphagia pattern and was correlated with clinical stage and treatment regimens including radiotherapy. Aspiration was more frequent in patients who had penetration and in older patients. In contrast to younger patients, older patients showed greater risk of aspiration even with a single abnormal swallowing irrespective of stage or treatment.